2021
DOI: 10.1016/j.heliyon.2021.e06677
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depression in South Asia during COVID-19: A systematic review and meta-analysis

Abstract: Introduction The COVID-19 pandemic has impacted biopsychosocial health and wellbeing globally. Pre-pandemic studies suggest a high prevalence of common mental disorders, including anxiety and depression in South Asian countries, which may aggravate during this pandemic. This systematic meta-analytic review was conducted to estimate the pooled prevalence of anxiety and depression in South Asian countries during the COVID-19 pandemic. Method We systematically searched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 127 publications
(229 reference statements)
5
72
4
2
Order By: Relevance
“…That is, the pooled prevalence rates for depression and anxiety were reported to be 48.2% (34.8 – 61.8%) and 52.3% (41 – 63.6%), respectively. 44 Although the present study rates seemed lower than the pooled rates, many people were still suffering from mental health problems.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…That is, the pooled prevalence rates for depression and anxiety were reported to be 48.2% (34.8 – 61.8%) and 52.3% (41 – 63.6%), respectively. 44 Although the present study rates seemed lower than the pooled rates, many people were still suffering from mental health problems.…”
Section: Discussioncontrasting
confidence: 65%
“…Considering the COVID-19-related psychiatric epidemiological studies of South Asian countries (including Bangladesh), a recent systematic review pooled the prevalence rates of depression and anxiety and found them to be 34.1% (28.9–39.4%) and 41.3% (34.7 – 48.1%) respectively. 44 The same study also observed that Bangladeshi people were the most psychologically vulnerable within this subcontinent. That is, the pooled prevalence rates for depression and anxiety were reported to be 48.2% (34.8 – 61.8%) and 52.3% (41 – 63.6%), respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Applying some of the mandatory restrictions, including social distancing at the earlier period of the pandemic inception, people started grabbing and worrying about their lives and personal safety, fear of getting infected, lost a beloved one, absence of appropriate treatment etc., which in uenced the risk of depression, anxiety and stress (17,45). Thus, participants belonging to general people, students etc.…”
Section: Discussionmentioning
confidence: 99%
“…generally increase psychological suffering, including post-traumatic stress disorder (PTSD), insomnia, phobia, fear, anxiety, depression etc. (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“… The authors have obviated meta-analysis of anxiety in the general population (Santabárbara et al (2020 1 )) and in specific populations like health workers (Santabárbara et al (2021 2 )) during COVID-19 outbreak that should be included in the introduction and discussion sections. In addition, a recent meta-analysis reported prevalence of anxiety in South Asia and also should be discussed (Hossain et al (2021 3 )). Data analysis: Please, replace ANOVA by t-test.…”
mentioning
confidence: 99%